Prisotnost protiteles proti virusu hepatitisa C pri asimptomatskih prejemnikih transfuzije krvi pred letom 1993 - Petek Šter, Marija (Zdravstveno varstvo, 2004)
Background. Hepatitis C is a liver infection transmitted mostly through blood and blood products. In Slovenia, mandatory large-scale testing of blood and blood products for hepatitis C was introduced in 1993. Before that date, getting hepatitis C from blood and blood products was much more likely, therefore pre-1993 blood recipients are considered a population group at increased risk for hepatitis C. The purpose of the study was to establish whether it is judicious to recommend blood testing for hepatitis C to asymptomatic individuals who received blood transfusion before 1993. Participants and methods. A questionnaire inquiring about blood transfusion received before 1993 was mailed to 1,241 individuals, aged 18 years and older,receiving primary health services at the Trebnje Health Centre. The response rate was 52,4% (651 respondents). Seventy-five (11,5%) subjects responded they had received blood transfusion before 1993, and 51 (68%) of them, aged 51 years on average, consented to blood testing for hepatitis C. Results. The most frequent reason for blood transfusion was surgery (45,3%), followed by pregnancy and birth (33,3%), injuries (18,7%), and anaemias (2,7%). Blood transfusion was received on average 19 years ago. In the group of pre-1993 blood recipients, none tested positive for hepatitis C. Conclusions. As indicated by the results of the study, there is no need to recommend asymptomatic pre-1993 blood transfusion recipients in Slovenia to have hepatitis C testing. Antibodies against hepatitis C virus are rarely present in the Slovene population, therefore a study on a larger group of younger pre-1993 blood transfusion recipients will be necessary to either confirm or refute the necessity of routine hepatitis C testing in asymptomaticindividuals treated by blood transfusion before 1993.
Keywords: hepatitis C; imunologija; kri; protitelesa; testiranje; transfuzija